2004
DOI: 10.1111/j.1523-1755.2004.00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic data of primary glomerular diseases in western France

Abstract: Between January 1, 1976, and December 31, 2002, histologic diagnosis of primary glomerular diseases (PGD) was made in 898 patients born and living at the time of diagnosis in a region of France, comprising 412,735 inhabitants, of whom 391,265 were aged from 10 to 85 years. The prevalence of PGD during a 75-year exposure to risk (10 to 85 years of age) was evaluated to 6.9 in 1000 (8.2 in 1000 males and 5.1 in 1000 females) during the 27-year period. The most common PGD was IgA nephropathy (IgAN) with a prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
104
3
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(128 citation statements)
references
References 3 publications
15
104
3
2
Order By: Relevance
“…Since 128,057,352 people resided in Japan in 2010, the estimated rate of renal biopsy was 140.6 to 164.0 per million population. This rate was higher than that in Romania [24], Spain [25], the Czech Republic [10], Denmark [26], and Scotland [27], was similar to that in France [28], and was lower than that in USA, Finland [29], and Australia [30].…”
Section: Discussion and Commentsmentioning
confidence: 60%
“…Since 128,057,352 people resided in Japan in 2010, the estimated rate of renal biopsy was 140.6 to 164.0 per million population. This rate was higher than that in Romania [24], Spain [25], the Czech Republic [10], Denmark [26], and Scotland [27], was similar to that in France [28], and was lower than that in USA, Finland [29], and Australia [30].…”
Section: Discussion and Commentsmentioning
confidence: 60%
“…IgA nephropathy is the most common primary glomerulopathy among all races from Europe [3][4][5], Asia [6,7], and Australia [8] with the exception of the black race [9]. Nair et al demonstrated that IgA nephropathy patients increase as the primary glomerulopathy among young adults (20-39 years old) in the USA [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, data from local or limited national registries of renal biopsy have been reported from South Korea [10,11], Bahrain [12,13], Brazil [14], Romania [15], China [16], Finland [17], Serbia [18], Pakistan [19] and Belgium [20]. Finally, there are also reports that include epidemiological data only on glomerular diseases from Australia [21], Macedonia [22], France [23], USA [24], Iran [25], Germany [26], Lebanon [27], Peru [28] and Poland [29]. In this study we describe the frequency and clinicopathological correlations of biopsy-proven native renal diseases in Croatian adults observed over past 15 years.…”
Section: Introductionmentioning
confidence: 99%